1996
DOI: 10.1136/jnnp.60.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal angioplasty for arteriosclerotic disease of the distal vertebral and basilar arteries.

Abstract: Objective-Percutaneous transluminal angioplasty (PTA) for the distal vertebral and basilar artery is now being performed in selected patients with haemodynamically significant lesions of the posterior cerebral circulation. Its effect and overall results were examined. Patients and methods-A balloon dilatation catheter specifically developed for these procedures, with a 240-3 5 mm balloon diameter, at 6 atmospheres of pressure, was used. Angioplasty was performed in 12 patients (including six whose initial resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 17 publications
0
44
1
Order By: Relevance
“…44 -49 Complication rates are estimated to be substantial and may stem from vessel rupture, thromboembolic events, or damage to small perforators and subsequent infarction. 45,47,48 It is only because the prognosis of basilar occlusion is so grave that these risks can be both tolerated and ethically justified. Our study documents the sequential use of chemical, followed by mechanical means of recanalization of the basilar artery.…”
Section: Percutaneous Transluminal Cerebral Angioplasty For Strokementioning
confidence: 99%
“…44 -49 Complication rates are estimated to be substantial and may stem from vessel rupture, thromboembolic events, or damage to small perforators and subsequent infarction. 45,47,48 It is only because the prognosis of basilar occlusion is so grave that these risks can be both tolerated and ethically justified. Our study documents the sequential use of chemical, followed by mechanical means of recanalization of the basilar artery.…”
Section: Percutaneous Transluminal Cerebral Angioplasty For Strokementioning
confidence: 99%
“…Touho [25] has reported a 38.5% restenosis rate for intracranial vessels of the anterior circulation. Terada, et al, [23] have reported one restenosis following angioplasty in 12 patients who underwent VB angioplasty; however, the immediate complication rate was 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Reserved for seriously ill, symptomatic patients, complication rates from angioplasty ranged from 12 to 33%. [8,13,23] Complications from angioplasty increase as angioplasty progresses in a rostral direction. Touho [25] has reported a 38.5% restenosis rate for intracranial vessels of the anterior circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with symptomatic or asymptomatic, severe intracranial atherosclerotic stenosis who were at high risk for stroke or death were included (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Intracranial Angioplasty and Stentingmentioning
confidence: 99%